Distinct cytokines balance the development of regulatory T cells and interleukin‐10‐producing regulatory B cells. Issue 4 (April 2014) - Holan, Vladimir; Zajicova, Alena; Javorkova, Eliska; Trosan, Peter; Chudickova, Milada; Pavlikova, Michaela; Krulova, Magdalena
Summary Regulatory T cells have been well described and the factors regulating their development and function have been identified. Recently, a growing body of evidence has documented the existence of interleukin‐10 (IL‐10) ‐producing B cells, which are called regulatory B10 cells. These cells attenuate autoimmune, inflammatory and transplantation reactions, and the main mechanism of their inhibitory action is the production of IL‐10. We show that the production of IL‐10 by lipopolysaccharide‐stimulated B cells is significantly enhanced by IL‐12 and interferon‐γ and negatively regulated by IL‐21 and transforming growth factor‐β. In addition, exogenous IL‐10 also inhibits B‐cell proliferation and the expression of the IL‐10 gene in lipopolysaccharide‐stimulated B cells. The negative autoregulation of IL‐10 production is supported by the observation that the inclusion of anti‐IL‐10 receptor monoclonal antibody enhances IL‐10 production and the proliferation of activated B cells. The effects of cytokines on IL‐10 production by B10 cells did not correlate with their effects on B‐cell proliferation or on IL‐10 production by T cells or macrophages. The cytokine‐induced changes in IL‐10 production occurred on the level of IL‐10 gene expression, as confirmed by increased or decreased IL‐10 mRNA expression in the presence of a particular cytokine. The regulatory cytokines modulate the number of IL‐10‐producing cells rather than augmenting or decreasing the secretion of IL‐10 on a single‐cell level. Altogether these data show that the production of IL‐10 by B cells is under the strict regulatory control of cytokines and that individual cytokines differentially regulate the development and activity of regulatory T cells and IL‐10‐producing regulatory B cells.